Zur Geschichte der Fachgruppe „Freie Forschungsinstitute“ in der Gesellschaft für Musikforschung - Dufner, Jens (Die Musikforschung, 2023)
The “Fachgruppe freie Forschungsinstitute” is one of the few permanent special interest groups within the “Gesellschaft für Musikforschung” (GfM). It represents research institutes in Germany which are not based at university departments (hence “free” institutes) and is thus concerned with institutional issues of long-term editorial projects. Furthermore, it serves as a forum for intense discussion of methodological and philological questions among its members. The group was founded in the mid-1960s, when the importance of research institutes had increased within musicology while their funding had not been secured yet. The association of the editorial projects with the German Academies of Science in the 1970s ensured their financial viability. Today the section is the central forum of exchange for musical philologists in Germany, regularly organising conferences and publishing scholarly volumes. As many of the long-term editorial projects are coming to an end and new projects are increasingly funded only short-term, the institutional function of the group has recently come back into focus.